1956
DOI: 10.1161/01.res.4.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Baroceptor Function in Chronic Renal Hypertension

Abstract: The results of these experiments indicate that the carotid and aortic baroceptor mechanisms are reset to the hypertensive pressure levels of animals with chronic perinephritic hypertension. Thus, seemingly, the buffer reflexes tend to maintain, rather than prevent, the chronic phase of renal hypertension and are, presumably, an important component in the mechanism of chronic renal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
152
1
3

Year Published

1963
1963
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(163 citation statements)
references
References 0 publications
7
152
1
3
Order By: Relevance
“…The efferent electroneurograms were processed and recorded as previously described. 8 " 6 The efferent signals were detected with an AC differential preamplifier (Model P-15, Grass Instrument Co., Quincy, MA) with a time constant of 3 msec. The amplified nerve spikes were displayed on an oscilloscope (Model R103N, Tektronix Inc., Beaverton, OR) for visualization and photographing (Tektronix Camera, Model C-12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efferent electroneurograms were processed and recorded as previously described. 8 " 6 The efferent signals were detected with an AC differential preamplifier (Model P-15, Grass Instrument Co., Quincy, MA) with a time constant of 3 msec. The amplified nerve spikes were displayed on an oscilloscope (Model R103N, Tektronix Inc., Beaverton, OR) for visualization and photographing (Tektronix Camera, Model C-12).…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting that centrally acting antihypertensive drugs, such as clonidine, L-dopa, and alpha-methyl dopa, effectively lower blood pressure in the SHR by suppressing SNA centrally (Judy, unpublished data). 6 These compounds presumably stimulate the central alpha adrenergic system, which lowers MAP by reducing peripheral sympathetic activity. 8 …”
mentioning
confidence: 99%
“…However, these changes are attenuated by the effects of baroreceptor resetting, whereby there is a shift in the function curve relating afferent baroreceptor activity to blood pressure, in the direction of the prevailing arterial pressure; estimates of the time course of baroreceptor resetting vary from minutes 6 to days or weeks. 7 Thus, as a result of resetting, the deleterious autonomic effects associated with initial doses of dihydropyridines may not persist with chronic therapy. In addition to the effects of resetting, the autonomic effects of dihydropyridine therapy may be reflected by changes in the gain or sensitivity of the baroreceptor reflex.…”
Section: Introductionmentioning
confidence: 99%
“…An initial alteration in arterial baroreceptor reflex whichis a major restraining mechanism of sympathetic activities wasan attractive hypothesis of a cause of essential hypertension (1). This idea, however, was hardly supported after it became clear that secondary baroreceptor resetting occurs rapidly and regularly in hypertension (4). Further, it was demonstrated that removal of arterial baroreceptors (sinoaortic denervation) in dogs did not cause a long-lasting elevation of the average blood pressure (5).…”
mentioning
confidence: 99%